GENDER ANALYSIS OF WOMEN’S AGENCIES (STUDY ON OPEN DEFECATION FREE - ODF CAMPAIGN IN BANDAR LAMPUNG CITY) - Dwi Wahyu Handayani; FENI ROSALIA (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This research is a gender analysis study of women’s agency in the Open Defecation Free (ODF) campaign, conducted by the first healthcare facility for the community, namely the Community Health Centre (pusat kesehatan masyarakat  or puskesmas) in Bandar Lampung City. ODF campaign officers are sanitarians and health promotion officers, most of whom are women. The ODF village program is a village where all people defecate in healthy latrines. The program is one of the pillars of the community-based total sanitation (Sanitasi Total Berbasis Masyarakat-STBM) policy, as an effort to realize the primary service transformation in the health sector launched by the Government of Indonesia since 2022. The descriptive qualitative research explores the experiences that include the contributions and challenges faced by women’s agency as sanitarians and health promotion officers in the ODF campaign. The researcher employed Naila Kabeer’s agency theory, which posits that agency is the ability to make decisions derived from cognitive processes, reflection, and analysis associated with the power within. The agency operates through the resources of a supportive social, political, and economic structure to shape the effectiveness of its transformative agency. The study demonstrates that political, social, and economic resources can support women’s agency among sanitarians and health promotion officers in the ODF campaign, thereby changing the construction of gender bias in the sanitation sector.